2003
DOI: 10.4049/jimmunol.171.9.4700
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α-Dependent ICAM-1- and VCAM-1-Mediated Inflammatory Responses Are Delayed in Neonatal Mice Infected with Pneumocystis carinii

Abstract: Neonatal mice have a delayed CD4-mediated inflammatory response to Pneumocystis carinii (PC) infection in the lungs that corresponds to a delayed TNF-α response and a delayed clearance of the organisms compared with adult mice. Since TNF-α is known to drive the up-regulation of adhesion molecules, we examined the expression and function of adhesion molecules in the lungs of neonatal mice. The expression of both ICAM-1 and VCAM-1 was significantly lower in the lungs of PC-infected neonatal mice compared with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 45 publications
6
53
0
Order By: Relevance
“…Induced expression of adhesion molecules, especially ICAM-1 and VCAM-1, have been reported to be associated with airway inflammatory responses (Ito et al, 2003;Lee et al, 2003;Qureshi et al, 2003). And, our previous study suggested a potential role of a PKCδ-p38 kinase-VCAM-1-linked cascade in the TNF-α-induced leukocyte adhesion and migration in the lung airway epithelium (Woo et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Induced expression of adhesion molecules, especially ICAM-1 and VCAM-1, have been reported to be associated with airway inflammatory responses (Ito et al, 2003;Lee et al, 2003;Qureshi et al, 2003). And, our previous study suggested a potential role of a PKCδ-p38 kinase-VCAM-1-linked cascade in the TNF-α-induced leukocyte adhesion and migration in the lung airway epithelium (Woo et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…4 Spleen cell migration is stimulated by mHEV cell secretion of the chemokine monocyte chemoattractant protein 1 (MCP-1). 15 The number of lymphocytes that migrate is linear from 0 to 24 hours followed by a plateau. 4 Spleen cells that migrate are more than 95% lymphocytes, 4 and the percentage of cells that migrate is consistent with other in vitro models with endothelial cell lines or cytokine-activated microvascular endothelial cells.…”
Section: Transwell Migration Assaymentioning
confidence: 99%
“…Migration was initiated by the addition of murine splenic lymphocytes (ϳ4 ϫ 10 6 cells) and erythrocytes (ϳ4 ϫ 10 6 cells; nonmigratory control), to the upper chamber of the transwell (29). Chemotaxis is induced by the constitutive expression of MCP-1 by the endothelial cell lines (31). Bile pigments and vehicle were present in both the upper and lower chambers throughout the duration of the experiment.…”
Section: Transwell Migration Assaymentioning
confidence: 99%